The Reality of Life in Kosdu, Anak Kalap Novel by Rodli TL: A Sociology of Literature Study - Sutardi Sutardi; Rodli Rodli; Isnaini Najmiatin; Serly Widia Astutik; Ahmad Yohandi (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
This study aims to determine the reality of live in the Kosdu, Anak Kalap includes the first reality of social, religius, and cultural life. Data collection teachniques used are reading and note-taking. Reading and note-tasking techniques are used to find out the reality of life contained in the kosdu novel. Based on the result of this study, it is konwn that there are several froms of life reality including the reality social, religius, and cultural life. The conclusions of some of these problem include the reality of social life reflected through social interactions carried out by the characters, the reality of religious life is reflected in the behavior and actions of the figures who are always submissive and obedient to the Islamic religion, the reality of cultural life is reflected through the beliefs of the characters in myths and kejawen value.